Developing Basic Educational Standards for Evaluation and Accreditation of Master of Sciences Course in Neonatal Intensive Care Nursing: A Report of a Delphi Study - Seyed Reza Mazloum; Maryam Ghorbanzadeh; Tayebeh Reyhani; Mehri Yavari; Hasan Boskabadi (Kerman University of Medical Sciences, 2016)
Background & Objective: Despite the importance of local educational standards for the correct implementation and evaluation of higher education programs studies show such standards do not exist for the masters degree in neonatal intensive care nursing Therefore the purpose of the present study was to develop basic educational standards for program evaluation and accreditation of the master of sciences course in neonatal intensive care nursing Methods: This study was a descriptive survey conducted using the Delphi survey method in 2014 A total of 20 experts including infants and medical education specialists administrators of the department of education faculty members of the department of pediatrics nursing administrators of neonatal intensive care units and students and graduates of the neonatal intensive care nursing course were selected through purposive sampling First items related to basic educational standards were extracted through an extensive review of databases Subsequently 3 sessions in 2 rounds were held with the experts and basic educational standards for the evaluation of the master of sciences course in neonatal intensive care nursing were developed on the basis of consensus Results: This study led to the proposal of 20 items as basic educational standards for the evaluation of the master of sciences course in neonatal intensive care nursing In the first round 25 items of the total 41 items were agreed upon by experts Statistical results showed the content validity index in clear expression importance and availability in the second round was 094 092 087 respectively Conclusion: Considering that the checklist of basic educational standards was developed by experts it is hoped it will gain high acceptability and be an efficient model for the evaluation of the masters program in neonatal intensive care nursing